Lymphangiogenesis in cervical cancer evaluated by expression of the VEGF-C gene in clinical stage IB-IIIB - Franc, Magdalena; Kachel-Flis, Agata; Michalski, Bogdan; Fila-Daniłow, Anna; Mazurek, Urszula; Michalski, Mateusz; Michalska, Anna; Kuczerawy, Ilona; Skrzypulec-Plinta, Violetta (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction : The aim of the present study was to evaluate the profile of VEGF-C gene expression in particular stages of cervical cancer (IB-IIIB) and to estimate the correlation between VEGF-C mRNA quantity profile and clinical stage. Material and methods : Material for molecular analysis consisted of cervical cancer tissue specimens collected from 38 women (10, 15, 13 cases were classified as IB, IIB and IIIB, respectively). The control group was composed of normal cervical tissues collected from 10 women who underwent hysterectomy for non-oncological reasons. The number of VEGF-C mRNA copies in particular groups was estimated by the reverse transcription quantitative polymerase chain reaction (RT-qPCR) method. Results: In the control group the average number of mRNA copies was 134 ± 36 (median: 106), in a group with stage IB it was 16 077 ± 7090 (median: 580), for stage IIB – 35 019 ± 8945 (median: 40 870). The highest number of mRNA VEGF-C copies was derived in a group of patients with cervical cancer of stage IIIB. The average quantity was 56 155 ± 12 470, whereas median 55 981. A statistically significantly higher level of VEGF-C gene expression was disclosed in cervical cancer specimens with stage IIB and IIIB than in the control group. In stage IIIB, the VEGF-C gene expression was significantly higher than in specimens derived from individuals in stage IB. Conclusions : In squamous cell carcinoma of the uterine cervix of stage IB-IIIB genes involved in lymphangiogenesis, especially VEGF-C , are expressed, which expression increases as the clinical stage of cervical cancer is higher.